Flexural Behavior of Concrete Members Reinforced With 3D-Textile Fibers-A Review - Abdulghani, Mays Rabea; Ali, Ahmed S. (Al-Nahrain Journal for Engineering Sciences, 2019)
Normal concrete is weak against tensile strength, has low ductility and also insignificant resistance to cracking. The addition of diverse types of fibers at specific proportions can enhance the mechanical properties as well as the durability. Discrete fiber, which is commonly used, have many disadvantages such as balling the fiber, random distribution, and limitation of the used Vf ratio. Based on this vision, a new technique was discovered, enhancing concrete by textile-fiber to avoid all the problems mentioned above. This paper presents all important consequence and conclusions obtained from previous studies on how to strengthen concrete with two-dimensional and three-dimensional textile-fibers, and focuses on the flexural behavior of concrete members. The results indicate that there was an improvement in flexural strength, deformation capacity, and toughness with different load conditions when using different types of textile-fiber. It was observed that the effect of textile-fibers would increase when this fiber was coated by epoxy. In TRC system, there is a significant impact on the number of textile-fiber layers used.